Sectoral and spatial patterns of Chinese cities' export structures. Issue 1 (2nd January 2020) - He, Canfei; Yu, Changda; Zhu, Shengjun
ABSTRACT: In the light of evolutionary economic geography, a city's export structure can reflect its capacity. Based on China's export data during 2001–2011, this paper examines the evolution of 338 Chinese cities' export structures, and their spatial patterns and product dynamics. By employing hierarchical clustering analysis and new indicators to measure Chinese's export product and destination structures, this paper shows that regional disparity in terms of export product and destination structures exists. More importantly, the evolution of Chinese cities' export structure is co-shaped by the process of convergence and divergence. We argue that regional disparity can be alleviated by reducing market segmentation and facilitating inter-city knowledge spillovers. Furthermore, the export product structures of Chinese cities are highly correlated with their export destination structures, indicating that export promotion policies should take into account both export product diversification and export market diversification.